2016
DOI: 10.18869/acadpub.ijrr.14.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Potent radioprotective effect of herbal immunomodulator drug (IMOD) on mouse bone marrow erythrocytes as assayed with the micronucleus test

Abstract: Background: Although numerous natural or synthe c drugs have been tested for their radioprotec ve capacity, yet no suitable drug has been introduced for rou ne clinical use. In this study the radioprotec ve effect of "a new herbal immunomodulator" commercially known as IMOD, specifically made to decrease the side effects of HIV virus, was inves gated on mouse bone marrow cells. Materials and Methods: Female NMRI mice (in a group of five) were exposed to 2 Gy gamma radia on following three days of intravenously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In the earlier study, Nair et al (2013) reported that mice exposed to ionizing radiation (2 Gy) displayed a significant increase in micronucleus in polychromatic erythrocytes when compared to normal control group. Similar observations were reported by Boroujeni et al where mice exposed to 2 Gy gamma radiation displayed significant rise in micronucleus in polychromatic erythrocytes at 24 and 48 h after radiation exposure (Boroujeni et al 2016). In the present study, similar findings were observed, as animals exposed to sublethal dose of X-rays (4 Gy) displayed significant increase (P ≤ 0.001) in the micronucleus in polychromatic erythrocytes (Fig.…”
supporting
confidence: 87%
“…In the earlier study, Nair et al (2013) reported that mice exposed to ionizing radiation (2 Gy) displayed a significant increase in micronucleus in polychromatic erythrocytes when compared to normal control group. Similar observations were reported by Boroujeni et al where mice exposed to 2 Gy gamma radiation displayed significant rise in micronucleus in polychromatic erythrocytes at 24 and 48 h after radiation exposure (Boroujeni et al 2016). In the present study, similar findings were observed, as animals exposed to sublethal dose of X-rays (4 Gy) displayed significant increase (P ≤ 0.001) in the micronucleus in polychromatic erythrocytes (Fig.…”
supporting
confidence: 87%
“…Although UD seed extract (UDSE) has been shown to exert antioxidant effects in experimental studies, there has been no adequate study of whether it has a protective role against DNA damage due to irradiation. In a study by Shakeri-Boroujeni et al (2016), a combination was tested as a radioprotective candidate in mice administered 2 Gy of radiation. In this herbal combination, UD was 1 among 3 other ingredients, and this combination was found to be effective in ameliorating the effects of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulatory effects in both the immune tissues in irradiated mice have been reported following the administration of the extract from Vernonia cinerea [ 103 ]. Recently, a potent radioprotective effect of a herbal drug prepared from Rosa canina , Urtica dioica , and Tanacetum vulgare , has been observed [ 104 ].…”
Section: Herbal Extractsmentioning
confidence: 99%